Analisis Return on Equity (ROE) pada Bank BTN Syariah tahun 2020–2024 - Rahma, Vellan Zunia; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This article analyzes Bank BTN Syariah's profitability ratio using Return on Equity (ROE) from 2020 to 2024. ROE started at 10.02% in 2020 during the pandemic challenges, increased sharply to a peak of 16.42% in 2022 during the economic recovery phase, reached an overall average profitability of 12.94% over five years, then declined to 10.76% in 2024 amid market pressures. The literature review examines several empirical studies that position ROE as a key profitability indicator for Islamic banking operations. The analysis results show a cyclical ROE pattern that displays a significant spike during the recovery implementation, then contrasted with a reversal of the decline during the recovery under stress conditions. Therefore, it requires a strategic equity management approach that targets sustainable performance, which exceeds the 15% profitability benchmark threshold for a competitive position in the Indonesian Islamic financial sector landscape